Randomized Trial of Ultralow vs Standard Pneumoperitoneum during Robotic Prostatectomy. Issue 3 (2nd September 2022) - Abaza, Ronney; Ferroni, Matthew C.
Abstract : Purpose: Laparoscopic and robotic surgery have traditionally been performed with pneumoperitoneum of 12–15 mmHg. Based upon our previous retrospective study showing an advantage to using ultralow pneumoperitoneum during robotic prostatectomy (RP), we performed a randomized, double-blinded, controlled trial of RP at 6 mmHg vs 15 mmHg to assess postoperative pain and opioid use. Materials and Methods: Patients undergoing RP with lymphadenectomy by a single surgeon were randomized to pneumoperitoneum pressures of 6 mmHg vs 15 mmHg. Pain scores and opioid use were recorded every 2 hours until discharge. Groups underwent intention-to-treat analysis on the primary outcome of pain scores up to 8 hours after post-anesthesia care unit. Results: A total of 138 patients were randomized to RP at 6 mmHg or 15 mmHg (67 and 71, respectively). Mean console time was 7 minutes longer at 6 mmHg (135 vs 128 minutes, p=0.02). Mean estimated blood loss was similar (p=0.4) with no transfusions in either group. Most patients were discharged on the same day as surgery (88% vs 84%, p=0.5). There was no statistically significant difference observed in morphine equivalents administered during surgery or used postoperatively, yet 6 mmHg patients had lower immediate (0–4 hours) mean pain scores (2.1 vs 3.5, p <0.01) and lower maximum pain scores (3.0 vs 5.2, p <0.01). Shoulder pain was lower in 6 mmHg patients (0.03 vs 0.15, p=0.01), as was groin pain (0.6 vs 1.2 p=0.01). Patients reported flatus earlier with 6 mmHg (mean 1.0 day vs 1.3 days, p <0.01). Conclusions: Pneumoperitoneum pressure of 6 mmHg during RP has several advantages over the commonly used level of 15 mmHg without any identified disadvantages. Surgeons should consider using lower insufflation pressures.